Penguatan Usaha Mikro Melalui Peningkatan Ekonomi Kreatif di Desa Lamu Kecamatan Tilamuta Kabupaten Boalemo - Abdussamad, Zuchri; Abdussamad, Juriko (Universitas Negeri Gorontalo, 2024)
Creative economy is a concept for realizing sustainable economic development based on creativity. Utilization of resources that not only renewable, but also unlimited, namely ideas, talent and creativity. The economic value of a product or service in creative era is no longer determined by raw materials or production systems as industrial era, but rather by utilizing creativity and creating innovation through increasingly advanced technological developments. Industry can no longer compete in the market by relying solely on price or product quality, but must compete based on creativity, innovation and imagination. In Lamu Village, Tilamuta District, there are two community micro business groups who really hope for assistance in the form of guidance, mentoring and training in strengthening micro businesses through improving the creative economy so that these businesses can be improved towards better development. Through the integrated KKN program, MBKM in Lamu village in 2022 can improve students' caring attitudes, empathy and the condition of the community's existence towards the economy in improving living standards through creative economic efforts. Activities will be carried out using a combination of community empowerment, training and mentoring methods involving students participating in the KKN MBKM Public Administration study program FIS UNG in Lamu village. The first step taken was to empower and provide assistance to the community, especially housewives who have micro businesses through the creative economy. The final target activities is to empower housewives who have micro businesses with a touch of science and technology from lecturers, students and the community by taking advantage of opportunities as a basis for the community's local economy, including utilizing coconut waste, namely coconut shells. Skills improvement is carried out through training in the field of production from coconut waste, namely coconut belts into cocopeat products. business management and marketing. Efforts to increase productivity through production assistance, improving product quality, introducing production equipment, creating brands and packaging, and market access. The conclusion of this activity has been the strengthening of the abilities and independence of communities operating in several small business sectors through a program to increase skills and productivity of the cocopeat business.Ekonomi kreatif adalah suatu konsep untuk merealisasikan pembangunan ekonomi yang berkelanjutan berbasis kreativitas. Pemanfaatan sumber daya yang bukan hanya terbarukan, bahkan tidak terbatas, yaitu, ide, gagasan, bakat dan kreativitas. Nilai ekonomi dari suatu produk atau jasa di era kreatif tidak lagi ditentukan oleh bahan baku atau sistem produksi seperti di era industri, tetapi lebih kepada pemanfaatan kreativitas dan penciptaan inovasi melalui perkembangan teknologi yang semakin maju. Industri tidak dapat lagi bersaing dipasar dengan hanya mengandalkan harga atau kualitas produk saja, tetapi harus bersaing berbasiskan kreativitas, inovasi dan imajinasi. Di Desa Lamu Kecamatan Tilamuta ada dua kelompok usaha mikro masyarakat sangat berharap adanya bantuan berupa pembinaan, pendampingan dan pelatihan dalam penguatan usaha mikro melalui peningkatan ekonomi kreatif sehingga usaha tersebut dapat ditingkatkan kearah pengembangan yang lebih baik. Melalui program KKN terintegrasi MBKM di Desa Lamu Tahun 2022 dapat meningkatkan sikap peduli, empati mahasiswa dan kondisi keberadaan masyarakat terhadap perekonomian dalam meningkatkan taraf hidup melalui usaha ekonomi kreatif. Kegiatan akan dilaksanakan dengan menggunakan perpaduan antara metode pemberdayaan masyarakat, diklat dan pendampingan dengan melibatkan Mahasiswa Peserta KKN MBKM program studi Administrasi Publik FIS UNG di desa Lamu. Langkah awal yang dilakukan adalah melakukan pemberdayaan dan pendampingan kepada masyarakat khususnya ibu rumah tangga yang memiliki usaha mikro melalui ekonomi kreatif. Target akhir dari kegiatan KKN-MBKM UNG Tahun 2022 ini adalah melakukan pemberdayan kepada ibu rumah tangga yang memiliki usaha mikro dalam sentuhan ilmu dan teknologi dari dosen mahasiswa dan masyarakat dengan memanfaatkan peluang sebagai basis ekonomi lokal masyarakat antara lain memanfaatkan sampah kelapa yakni kulit kelapa. Peningkatan ketrampilan yang dilakukan melalui pelatihan di bidang produksi dari hasil limbah kelapa, yakni sabuk kelapa menjadi produk cocopeat. manajemen usaha serta pemasaran. Upaya peningkatan produktivitas melalui pendampingan produksi, peningkatan kualitas produk, introduksi peralatan produksi, pembuatan merek dan kemasan, serta akses pasar. Kesimpulan dari kegiatan ini telah terjadi penguatan kemampuan dan kemandirian masyarakat yang bergerak di beberapa sektor usaha kecil melalui program peningkatan ketrampilan dan produktivitas usaha cocopeat.